IMPLEMENTATION OF THE LEARNING CYCLE 5E LEARNING MODEL DURING THE COVID-19 PANDEMIC (MULTICASE STUDY OF MOTIVATION AND LEARNING PARTICIPATION) - Muhammad Faishal; Budiyono Saputro (Institut Keislaman Abdullah Faqih Gresik, 2021)
Abstract: This study aims to determine the implementation of the Learning Cycle 5E learning model during the Covid-19 pandemic for Islamic Religious Education class XI subjects. There are several main things in this study, namely: 1) the implementation of the 5E Learning Cycle learning model during the Covid-19 pandemic, 2) the supporting factors and inhibiting factors for the implementation of the 5E Learning Cycle learning model during the Covid-19 pandemic, 3) the motivation and participation in learning Religious Education Islam Class XI students during the Covid-19 pandemic at SMA Negeri 2 Ungaran, SMA Negeri 1 Tuntang, and SMA Negeri 1 Ambarawa. The author uses a qualitative approach to collect data from educators. The findings of this study are the implementation of the Learning Cycle 5E learning model during the Covid 19 pandemic carried out with an online learning system. In this case, it does not reduce the learning steps in the 5E Learning Cycle model. There are several inhibiting factors in the implementation of the 5E Learning Cycle model during the Covid 19 pandemic, but there are also supporting factors so that the learning process can run optimally. The application of the Learning Cycle 5E learning model during the Covid-19 pandemic makes learning more student centered than face-to-face learningKeyword: 5e learning cycle model, learning during the covid-19 pandemic, Learning Islamic education